Comorbidities in a cohort of privately insured South Africans with systemic lupus erythematosus - Ntumba, Mbombo Henriette Ngandu (My University, 2024)
Background: Comorbidities in systemic lupus erythematosus (SLE) impact negatively health related quality of life and life expectancy. We undertook a retrospective study of the burden of comorbidities in privately insured South Africans with SLE. Methods: Data review of patients insured with Discovery Health Medical Scheme (DHMS), ≥16years at diagnosis, ≥6months follow-up and diagnosed with SLE based on ICD 10 codes. Demographics, drug therapy and comorbidities listed in the Charlson Comorbidity Index (CCI) and other comorbidities occurring commonly in SLE patients were documented. Results: Of 520 patients with SLE ICD 10 codes, only 207 met the other inclusion/exclusion criteria for data analysis. Most were women (90.8%), median (IQR) age and follow-up duration of 39 (30.3-53.0) and 6.1 (3.7-8.1) years, respectively. All patients had at least one comorbidity, the most frequent CCI comorbidities being pulmonary disease (30.9%), congestive heart failure (CHF) (15%) and renal disease (14.5%). Common CCI comorbidities were hypertension (53.1%), mood and anxiety disorders (46.9%), infections (urinary tract infections (UTI) (37.7%) and pneumonia (33.8%)). Independent predictors of 1) CHF were renal disease (OR=855), dyslipidaemia (OR=15.3) and male gender (OR=43.0); 2) hypertension were age at diagnosis (OR=1.03), type 2 diabetes (OR=4.45) and renal disease (OR=4.34); and 3) mood and anxiety disorders were female gender (OR=3.98), cerebrovascular accident (OR=3.18), UTI (OR=2.39) and chloroquine use (OR=1.94). Conclusion: Comorbidities in this cohort of privately insured South Africans with SLE were common, with all patients having at least one comorbidity. Hypertension, infections and mood and anxiety disorders were the leading comorbidities.
A research report submitted in partial fulfilment of the requirement for the degree of Master of Medicine (MMed) in Internal Medicine to the Faculty of Health Sciences, University of the Witwatersrand, School of Clinical Medicine, Johannesburg, 2023
Keywords: Systemic lupus erythematosus; Comorbidities; Africa; SDG-3: Good health and well-being; SDG-16: Peace, justice and strong institutions